RESETTLEMENT OF THE KALMYKS IN THE VOLGO-URAL INTERFLUVE IN THE XVII-XVIII CENTURIES: PROBLEMS OF INTERACTION WITH THE NEIGHBORING PEOPLES IN THE CONTEXT OF RUSSIAN FOREIGN POLICY - K. Koltsova; P. Koltsov (Гуманитарные и юридические исследования)
This article discusses issues related to the date and reasons for the appearance of the Kalmyks in the Volga-Ural interfluve in the XVII-XVIII centuries. The authors addresses the problem of the relations between the Kalmyks and the neighboring peoples in the context of Russian foreign policy. As a result of a number of successful actions, both military and diplomatic, the Kalmyks settled in the areas near the Emba, Yaik and Volga rivers, displacing the Nogai clans from their homes. The main reasons why the Kalmyks sought to gain a foothold in the above territories were not only vast pastures bordering the sea, but also relatively little competition from neighboring nomadic peoples (in particular, the Nogais and the Bashkirs). The authors reasonably note that in the current situation the Russian government did not have an opportunity to banish the newcomers by force, therefore, recognizing the right of the Kalmyks to roam these territories, they began to bring the Kalmyk cavalry as a military force to protect the southern borders of the empire, including the suppression liberties on the part of the Nogais, "reconciliation" of the Kazakhs, campaigns against the Crimean Khanate, etc. Defending the southern borders of Russia from its external enemies, the Kalmyks nevertheless took an active part in such social forms of protest as the Cossack-peasant uprising led by Emelyan Pugachev. Thus, the resettlement of the Kalmyks in the XVII century to the areas of the Emba, Yaik, and Volga rivers opened new pages in the relations of the Kalmyks with the neighboring peoples. The main feature of this period was the resettlement and residence of the Kalmyks in the above-mentioned areas (as evidenced by the toponomic names of these places) and the entry of the Kalmyk people into the Russian Empire. Moreover, the early period of this relationship is characterized by frequent military clashes between the Kalmyks and the neighboring peoples over pasture lands, cattle theft and political predilections. Gradually, the above-mentioned peoples went through a complex process of integration into the Russian state, but at the same time continuing to maintain their ethnocultural and economic characteristics.